Surgical technique: an improvisation in application of the technique of core-cut fistulectomy for fistula-in-ano. Issue 3 (29th March 2021) - Parwez, Masoom; Huda, Tanweerul; Mital, Kushal; Pandya, Bharati
Abstract: Cryptoglandular fistula-in-ano is a chronic inflammatory condition of the perianal region attributed to the obstruction of the glands, located chiefly at the dentate line and their subsequent infection. Anal fistulae are difficult to treat, and minimally invasive procedures are evolving with promises. We present an improvised application of core-cut technique of fistulectomy. It is a minimally invasive, simple, effective and easy to perform procedure with minimal risk of incontinence and recurrence in simple cryptoglandular fistulae-in-ano. We performed 47 cases with good results and present this procedure to emphasize the procedural modification used.